Optimizing the Recruitment and Selection Process for Contract-based Civil Servant among Existing Non-Permanent Staff - Mukarom, M. Multazam All; Sufianti, Ely; Pradesa, Hafid Aditya; Afandi, Muhamad Nur; Rahman, Abdul (Image : Jurnal Riset Manajemen, 2024)
This study aimed to optimize the recruitment and selection process for Government Employees with Work Contracts (PPPK) from existing honorary workers in Pagar Alam City Government. The policy to eliminate honorary workers, scheduled for completion by December 2024, has accelerated the transition of honorary workers to PPPK status through the recruitment process. However, the implementation of this policy faces various challenges, including a lack of detailed regulations, misalignment between administrative requirements and job needs, and uncertainties in the implementation timeline. Employing a descriptive qualitative approach, supplemented by a quantitative questionnaire, this research analyzed the person-job fit. The findings suggest that optimization can be achieved through the administrative selection stage by providing flexibility in assessing work experience and offering video tutorial-guided registration assistance. Furthermore, to ensure the quality of recruited PPPKs, an Additional Technical Competency Test (SKTT) is recommended to assess candidates' substantial competencies beyond basic qualifications. This research contributes significantly to improving the PPPK recruitment process, particularly for local governments undergoing the transformation of honorary workers. The recommendations produced can serve as a reference in developing more effective and efficient recruitment policies and procedures.